Furofuranoid-Type Lignans and Related Phenolics from Anisacanthus virgularis (Salisb.) Nees with Promising Anticholinesterase and Anti-Ageing Properties: A Study Supported by Molecular Modelling - Mohamed A. A. Orabi; Reda A. Abdelhamid; Hanan Elimam; Yaseen A. M. M. Elshaier; Ahmed A. Ali; Nayef Aldabaan; Abdulaziz Hassan Alhasaniah; Mohamed S. Refaey (Plants, 2024)
Lignan phytomolecules demonstrate promising anti-Alzheimer activity by alleviating dementia and preserving nerve cells. The purpose of this work is to characterize the lignans of Anisacanthus virgularis and explore their potential anti-acetylcholinesterase and anti-ageing effects. Phytochemical investigation of A. virgularis aerial parts afforded a new furofuranoid-type lignan (1), four known structural analogues, namely pinoresinol (2), epipinoresinol (3), phillyrin (4), and pinoresinol 4-O-β-d-glucoside (5), in addition to p-methoxy-trans-methyl cinnamate (6) and 1H-indole-3-carboxaldehyde (7). The structures were established from thorough spectroscopic analyses and comparisons with the literature. Assessment of the anticholinesterase activity of the lignans 1–5 displayed noticeable enzyme inhibition of 1 (IC50 = 85.03 ± 4.26 nM) and 5 (64.47 ± 2.75 nM) but lower activity of compounds 2–4 as compared to the reference drug donepezil. These findings were further emphasized by molecular docking of 1 and 5 with acetylcholinesterase (AChE). Rapid overlay chemical similarity (ROCS) and structure–activity relationships (SAR) analysis highlighted and rationalized the anti-AD capability of these compounds. Telomerase activation testing of the same isolates revealed 1.64-, 1.66-, and 1.72-fold activations in cells treated with compounds 1, 5, and 4, respectively, compared to untreated cells. Our findings may pave the way for further investigations into the development of anti-Alzheimer and/or anti-ageing drugs from furofuranoid-type lignans.